Estudio de factibilidad para un parque acuático en el cantón Manta, provincia Manabí - Basurto Bravo, Isabel Yaqueline (2015)
The purpose of the present research is to determine the feasibility of an aquatic park in Manta Canton, with the purpose of establishing its economic viability. For the sustenance of the study, the theoretical framework was elaborated by means of an analysis of bibliographical aspects and references. The methodology applied corresponds to a field and descriptive research; the applied methods were scientific, inductive and deductive, technics and tools like observation, interviews and direct observation were used. For the development of the investigation, it started from a situational diagnosis describing the physical and demographic characteristic of the canton; followed by an internal and external analysis of the tourist sector through the elaboration and analysis of the SWOT matrix, proceeding with a market study, where the offer was analyzed, demands and competition, by means of a survey applied to local and national tourists to identify their likes and preferences; an observation record was applied to the recreation establishments, obtaining the competitive profile. Consecutively it carried out an analysis of technical feasibility with which was determined the size, distribution and engineering of the project, an analysis of the physical-environmental impacts was elaborated through the Leopold Matrix. Then proceeded to make an analysis of economic-financial feasibility using several indicators. This determined the feasibility of the project, which gave the viability of the aquatic park in Manta Canton.